Effects of pressure and strain on spin polarization of IrMnSb. (29th December 2016) - Tutic, Ibrica; Herran, Juliana; Staten, Bradley; Gray, Paul; Paudel, Tula R; Sokolov, Andrei; Tsymbal, Evgeny Y; Lukashev, Pavel V
Abstract: A high degree of spin polarization in electron transport is one of the most sought-after properties of a material which can be used in spintronics—an emerging technology utilizing a spin degree of freedom in electronic devices. An ideal candidate to exhibit highly spin-polarized current would be a room temperature half-metal, a material which behaves as an insulator for one spin channel and as a conductor for the other spin channel. In this paper, we explore a semi-Heusler compound, IrMnSb, which has been reported to exhibit pressure induced half-metallic transition. We confirm that the bulk IrMnSb is a spin-polarized metal, with dominant contribution to electronic states at the Fermi energy from majority-spin electrons. Application of a uniform pressure shifts the Fermi level into the minority-spin energy gap, thus demonstrating pressure induced half-metallic transition. This behavior is explained by the reduction of the exchange splitting of the spin bands consistent with the Stoner model for itinerant magnetism. We find that the half-metallic transition is suppressed when instead of uniform pressure the bulk IrMnSb is exposed to biaxial strain. This suppression of half-metallicity is driven by the epitaxial strain induced tetragonal distortion, which lifts the degeneracy of the Mn 3 d t 2g and e g orbitals and reduces the minority-spin band gap under compressive strain, thus preventing half-metallic transition. Our calculations also indicate that in thin film geometry, surface states emerge in the minority-spin band gap, which has detrimental for practical applications impact on the spin polarization of IrMnSb.